2017
DOI: 10.1007/s11999-016-4792-5
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible and Safe to Perform Acetabular-preserving Resections for Malignant Neoplasms of the Periacetabular Region?

Abstract: Background Primary malignant tumors located near the acetabulum are usually managed by resection of the tumor with wide margins that include the acetabulum. These resections are deemed P2 resections by the Enneking and Dunham classification. There are various methods to perform the subsequent hip reconstruction. Unfortunately, there is no consensus as to the best management. In general, patients undergoing resection at this level will have substantial levels of pain and disability as measured by the Musculoske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…Marginal and intralesional resection may result in 70%–100% local recurrence 15,16. Consequently, accurate preoperative imaging assessment is vital for bone tumors 17,18. CT and MRI are the most effective modalities for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Marginal and intralesional resection may result in 70%–100% local recurrence 15,16. Consequently, accurate preoperative imaging assessment is vital for bone tumors 17,18. CT and MRI are the most effective modalities for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the local recurrence rate and improve the hip function, wide resection should be performed; meanwhile, traditional wide resection of region II should be avoided. In a study of five patients with malignant neoplasms of the periacetabular region, Lam et al [ 9 ] performed acetabular-preserving resections that preserved the weight-bearing acetabulum, and satisfactory outcomes were obtained with a median follow-up of 37 months. Gerbers and Jutte [ 10 ] reported one patient with chondrosarcoma of the region III treated by partly resecting the frontal part of the acetabulum with computer assistance to obtain a safe margin and achieved an excellent postoperative function with a follow-up of 3.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…This can provide precise imaging and achieve desired safe margins. Lam et al [ 9 ] reported that the precise planning of the resection was carried out with computer navigation software. In the current study, we use the Mimics software to visualize and segment the CT images and render 3D pelvic bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations